What Motivates Companies to Avoid Tax? - Yenny Rachmad; Nuraini A Nuraini A; Fifi Yusmita (Universitas Pendidikan Indonesia, 2023)
Main Purpose - This study looks into whether transfer pricing, corporate social responsibility, and leverage are factors that motivate companies to undertake tax avoidance of non-financial companies on the Indonesia Stock Exchange (IDX).Method - The sample consisted of 86 companies that were randomly selected by simple random sampling from 2017 to 2019. A total of 603 data observations consisting of the annual reports of 52 domestic companies and 34 multinational companies were analyzed by use of multiple linear regression with IBM SPSS 21 software.Main Findings – This study implies that the majority of companies consider the practice of tax avoidance to be unethical, the results show that the tier of tax-avoidance practices in companies that are listed on the IDX is very low. On the other hand, transfer pricing, corporate social responsibility, and leverage do not affect tax avoidance since those are not factors that cause companies to avoid taxes.Theory and Practical Implications - Most companies in Indonesia view tax avoidance as unethical even though it is legal. These findings are expected to contribute to regulators in setting tax-avoidance arrangements in Indonesia.Novelty - Compared to other studies, this study examines tax avoidance practices from an ethical perspective.